Introduction of loan-based crowdfunding as an alternative source of funds for MSMEs for the Kediri Raya Culinary Group - Kartika Yuliari; Damar Nindi Vaulia Puspita; Dwi Juwarni; Rosadila Adetiana Susanto; Handry Valentino Saiang (Universitas Muhammadiyah Magelang, 2022)
MSMEs have characteristics that can help them survive in times of crisis. This happens because the smaller size of the organization makes it possible to do something flexible when a threat or opportunityis present. The problem experienced by MSMEs of the Kediri Raya Culinary Group is that it has difficulty to get business capital credit from banking for business capital. The long barrage of regulatory and administrative processes of banking became a trigger for difficulties. This activity aims to provide solutions to MSMEs as an alternative source of business capital funds. The method used is a survey method with the form of interview activities about MSME knowledge about loan-based crowdfunding financing; community development; focus discussion group; and mentoring. This activity can increase the knowledge / insights of MSME actors about loan-based crowdfunding financing as an alternative source of funds. This activity also provides convenience in obtaining business capital and can minimize losses and risks in obtaining loan funds. The development of this activity can maintain and develop the business of MSMEs of the Kediri Raya Culinary Group.